2010
DOI: 10.1007/s13139-010-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Fluorodeoxyglucose Uptake and Glucose Transporter-1 Expression in Gastric Signet Ring Cell Carcinoma

Abstract: Purpose Gastric signet ring cell carcinoma (GSRC) is known to have low fluorodeoxyglucose (FDG) uptake. The aim of the study was to investigate the relation between FDG uptake and glucose transporter (GLUT)-1 expression and clinicopathologic parameters in cases of GSRC. Materials and Methods Forty patients (28 men, mean age 54±12 years) with histologically confirmed GSRC who underwent pre-operative [18 F]FDG PET/CT were enrolled. Maximum standardized uptake values (SUVmax) were compared with clinicopathologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…Korean studies have suggested that the intestinal type of gastric cancer is related to GLUT-1 [14,16,40]. Our study also obtained a similar result: multivariate analysis of overall or advanced stage gastric cancer revealed that the positive rate of GLUT-1 in intestinal gastric cancer was higher than that in the diffuse type.…”
Section: Discussionsupporting
confidence: 85%
“…Korean studies have suggested that the intestinal type of gastric cancer is related to GLUT-1 [14,16,40]. Our study also obtained a similar result: multivariate analysis of overall or advanced stage gastric cancer revealed that the positive rate of GLUT-1 in intestinal gastric cancer was higher than that in the diffuse type.…”
Section: Discussionsupporting
confidence: 85%
“…False negative PET CT is common in mucin secreting signet ring cell adeno carcinoma due to GLUT-1 transporter deficiency. Gastric signet ring cell carcinoma (GSRC) is known to have low fluorodeoxyglucose (FDG) uptake (9). Staging laparoscopy is performed prior to definitive surgery.…”
Section: Staging and Diagnosismentioning
confidence: 99%
“…In gastric cancer, the degree of glucose transporter 1 (GLUT1) expression is also different in different pathological types. The expression level of GLUT1 in highly differentiated gastric cancer cells is higher than that in gastric signetring cell carcinoma, therefore, the latter has lower results for 18F-FDG uptake [23]. In addition, compared with other histological types of gastric cancer, pyruvate kinase M2 (PKM2) subtype in signet-ring cell carcinoma is at a low expression level [24].…”
Section: Discussionmentioning
confidence: 99%